**Answer:**

x = -3 ; y = -6

**Step-by-step explanation:**

x = y + 3

-2x + 4y = -18

-2(y+3) + 4y = -18

-2y -6 + 4y = -18

2y = -12

y = -6

x = -6+3

x = -3

**Step-by-step explanation:**

The answer is

If you need any explanation in it or anything on math you can communicate with me on Whats on this number +201557831028 or in email or face or anything.

I can help you solve what you want in mathematics in exchange for some money. If you want to, you can inform me about it and I will help you.

O.9c

Step-by-step explanation:

**Answer:**

x = 9

**Step-by-step explanation:**

Since we know that the triangle is a right triangle we also know that the angle would be 90 degrees

However we are only given 56 and 3x+7

Let 3x+7 be u

We know that 56+u=90 so solve for u

u=90-56

u = 34

Now u = 3x + 7 so,

3x + 7 = 34

solve for x,

3x=34-7

3x=27

x=27/3

**x=9.**